2019
DOI: 10.7567/1347-4065/ab51b5
|View full text |Cite
|
Sign up to set email alerts
|

Spin orbit torques in ferrimagnetic GdFeCo with various compositions

Abstract: Compositional dependence of spin–orbit torque (SOT) of the bilayer comprised of Ta and ferrimagnetic GdFeCo was investigated. Critical current density of SOT switching Jsw of the GdFeCo/Ta bilayers did not vary with Gd composition x, and were found to exhibit roughly Jsw = 11 MA cm−2. Two orthogonal components of SOT, damping-like torque τDL and field-like torque τFL were estimated by measuring harmonic Hall resistance under in-plane fields parallel and perpendicular to the AC current, respectively. The absolu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 36 publications
2
6
0
Order By: Relevance
“…While the M s was minimum, the coercive fields reached their maximum at magnetic compensation composition. 19,20 The angular momentum compensation composition ( x AMC ) was determined using the following equations: M = M Gd + M FeCO where A i = M i / γ i , also M i (i = Gd or FeCo) is the magnetic moment and γ i = g i μ B / ħ is the corresponding g factor, and μ B and ħ are the Bohr magnetron and Planck constants, respectively. The g factor is g Gd ≈ 2.0 and g FeCo ≈ 2.16, 21,22 hence, the x AMC was estimated to be x AMC ∼ 23, as indicated in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…While the M s was minimum, the coercive fields reached their maximum at magnetic compensation composition. 19,20 The angular momentum compensation composition ( x AMC ) was determined using the following equations: M = M Gd + M FeCO where A i = M i / γ i , also M i (i = Gd or FeCo) is the magnetic moment and γ i = g i μ B / ħ is the corresponding g factor, and μ B and ħ are the Bohr magnetron and Planck constants, respectively. The g factor is g Gd ≈ 2.0 and g FeCo ≈ 2.16, 21,22 hence, the x AMC was estimated to be x AMC ∼ 23, as indicated in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Note that all measurements are performed at room temperature. 19,20 . The angular momentum compensation composition (x AMC ) was determined using the following equations:…”
Section: The Composition Of the Films Was Measured By Energy Dispersi...mentioning
confidence: 99%
See 1 more Smart Citation
“…We initially discern the magnetic properties of Gdx(Fe88Co12)100-x films. Figure 2 25,26 . The angular momentum compensation composition (xAMC) was determined using the following equations:…”
Section: Design and Sample Characterizationmentioning
confidence: 99%
“…It has been shown that there is a possibility of ultra-fast switching magnetization by a femtosecond laser [9,21], which is promising for data storage. In addition, the widely varying stoichiometric composition provides opportunities to control the magnetic and spin transport properties of GdFeCo films [22,23]. In the presence of a perpendicular oriented external magnetic field, the GdFeCo alloy demonstrates the presence of a triple phase transition point with respect to the change of the external magnetic field (H) and the stoichiometric coefficient in the Gd x (FeCo) 1-x (x).…”
Section: Introductionmentioning
confidence: 99%